∫ 0 1 ∫ 0 1 ∫ 0 1 1 + x 2 y 2 z 2 d x d y d z π 3 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Could you also explain how β ( 3 ) is calculated?
Log in to reply
I had only looked it up. Can you direct me to a proof?
Log in to reply
I couldn't find a proof either.
Log in to reply
@Digvijay Singh – You could use the trilogarithm function. The summation is the immaginary part of (Li(i)-Li(-i))/2. (Here Li denotes the trilogarithm function) And we have the functional equation Li(-z)-Li(-1/z)= (-1/6)(ln(z))^3 -1/6(pi^2)(ln(z)) Now substitute z= -i to get the value. And make sure to evaluate only the principal value of ln(i) otherwise it leads to infinite solutions.
Problem Loading...
Note Loading...
Set Loading...
∫ 0 1 ∫ 0 1 ∫ 0 1 1 + x 2 y 2 z 2 d x d y d z = ∫ 0 1 ∫ 0 1 ∫ 0 1 n = 0 ∑ ∞ ( − 1 ) n ( x y z ) 2 n d x d y d z =
n = 0 ∑ ∞ ( − 1 ) n ∫ 0 1 ∫ 0 1 ∫ 0 1 ( x y z ) 2 n d x d y d z = n = 0 ∑ ∞ ( 2 n + 1 ) 3 ( − 1 ) n
Now this is the Dirichlet Beta Function: β ( s ) = n = 0 ∑ ∞ ( 2 n + 1 ) s ( − 1 ) n β ( 3 ) = 3 2 π 3